Urgent psychiatric consultations for suicide attempt and suicidal ideation before and after the COVID-19 pandemic in an Italian pediatric emergency setting - Apicella, Massimo; Serra, Giulia; Trasolini, Monia; Andracchio, Elisa; Chieppa, Fabrizia; Averna, Roberto; Iannoni, Maria Elena; Infranzi, Antonio; Moro, Marianna; Guidetti, Clotilde; Maglio, Gino; Raucci, Umberto; et al. (Frontiers in Psychiatry, 2023)
Introduction Suicidal attempts (SAs) in youth have been increasing during the last decades. Methods We studied consultations, SA, and suicidal ideation (SI) in a pediatric emergency department (ED). Results From 1 January 2011 to 31 May 2022, 606,159 patients accessed the ED, 8,397 of who had a child psychiatry consultation (CPC). CPCs increased significantly by 11 times in the last decade (155 in 2011 vs. 1,824 in 2021, p < 0.001); CPCs for SA increased significantly by 33 times, from 6 in 2011 to 200 in 2021 (3.9% of total CPC vs. 11%, p < 0.001). While total CPCs increased constantly during the entire period (annual percent change (APC) of 21.7 from 2011 to 2021 in a 0 joinpoint model), CPCs for SA increased significantly from 2011 to 2016, were approximately stable from 2016 to 2020, and then had a peak in 2021 after the COVID-19 pandemic (APC from 2011 to 2016 of 64.1, APC of 1.2 from 2016 to 2020, and APC of 230 after 2020 in a 2-joinpoint model). Discussion Total CPCs in ED as well as evaluation for SA and SI increased significantly during the last decade. CPCs for SA had an additional increase after the COVID-19 pandemic. This picture warrants timely and efficient improvements in emergency settings and mental health resources.